2015
DOI: 10.1007/s10493-015-9892-5
|View full text |Cite
|
Sign up to set email alerts
|

An update on the ecological distribution of the Ixodidae ticks in Zimbabwe

Abstract: In total 7 567 were collected from 121 dip tanks in 12 districts representative of Zimbabwe's five ecological regions between September 2013 and May 2014. Based on morphological traits four genera and 13 species of ticks were identified. Amblyomma hebraeum (60.3%), Rhipicephalus microplus (58.7%), Rhipicephalus decoloratus (47.1%), Rhipicephalus appendiculatus (56.2%), Rhipicephalus evertsi evertsi (67.8%), Rhipicephalus (near) punctatus (13.2%), Hyalomma truncatum (38%) and Hyalomma rufipes (46.3%) were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…In this study, the most abundant tick species was R. evertsi evertsi and it has also been previously reported by Sungirai et al [53] and Mediannikov et al [54] to be one of the most prevalent ticks that parasitize both domestic and wild animals. There are scanty reports on the ability of this species to transmit diseases in both humans and animal.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the most abundant tick species was R. evertsi evertsi and it has also been previously reported by Sungirai et al [53] and Mediannikov et al [54] to be one of the most prevalent ticks that parasitize both domestic and wild animals. There are scanty reports on the ability of this species to transmit diseases in both humans and animal.…”
Section: Discussionsupporting
confidence: 88%
“…The epidemiology of these diseases has been studied in the past (Katsande et al, 1999a;Latif et al, 2001;Norval et al, 1984a;Peter et al, 1998). Tick-borne diseases are responsible for more than 60% of all cattle mortalities in the country (Sungirai et al, 2015). This has led to the government playing a central role in tick control programs in communal areas and A1 resettlement areas, where they co-ordinate the purchase and supply of acaricides.…”
Section: Introductionmentioning
confidence: 99%
“…(B.) microplus in South Africa (Tønnesen et al, 2004;Horak et al, 2009;Nyangiwe et al, 2013a;Nyangiwe et al, 2017), Tanzania (Lynen et al, 2008), Zimbabwe (Smeenk et al, 2000;Sungirai et al, 2015) and West Africa (Madder et al, 2007(Madder et al, , 2012Adakal et al, 2013) is one such example. Recently, farmers encountered tick resistance to the use of acaricide in Burkina Faso, Mali and Togo.…”
Section: Acaricide Resistance In Rhipicephalus (Boophilus) Microplus mentioning
confidence: 99%
“…) microplus (Barré & Uilenberg, 2010). In Zimbabwe, A. variegatum is colonizing territories in which it was not found previously (Estrada-Peña et al, 2008;Sungirai et al, 2015). However, numerous studies have shown that cattle with smooth light-coloured short-hair coats (Nguni and Boran breeds) tend to have lower tick infestations than those with rough darker-coloured long-hair coats (Martinez et al, 2006;Muchenje et al, 2008;Katiyatiya et al, 2014).…”
Section: Introductionmentioning
confidence: 98%